Spoken word production: Processes and potential breakdown - Biedermann, Britta; Fieder, N.; Nickels, L. (2018)
Introduction: The processes of spoken word production have been a focus of interest for decades and this research has been summarised in several reviews (e.g., Friedmann, Biran, & Dotan, 2013; Nickels, 1997, 2001a,b; Wilshire, 2008). However, many questions remain unanswered and consequently spoken word production remains an area of research interest, informed by data from unimpaired and impaired adult language, as well as language development. Several theories of spoken language production have been proposed over the last half century, each differing slightly in levels of representation, processing steps, and activation flow. In this chapter, we focus on four of the most influential theories of spoken language production.